Relações de gênero e sexualidades na formação docente: (des)construção de saberes das graduandas do curso de pedagogia - Silva, Neiva Maria Rodrigues (2017)
The aim of this research was to discuss the experiences built by the students of the Education course at Centro Universitário de Formiga around the gender and sexuality topics linked to the deployment phase of the subjects Education and Diversities at the beginning of the students study. The methodological procedures of this research involved the help of the 3 period of the Education course students whom wrote a logbook that could be used as the main register tool which made up the empirical evidence for the quantitative research. The logbook was a key mechanism to the involved people, especially to the researcher who could register her perceptions, opinions, feelings towards the shared experiences and discussions in the meetings related to the topics. The activities were developed in five meetings included in the hours schedule of the Education and Diversity subjects. The found results were treated in qualitative form through the critical methodology.In particular inspired by the studies of the researchers Dagmar Estermann Meyer and Marlucy Alves Paraíso, which made possible to analyze the students notes and their reports. It is hoped the discussion in this present work can contribute to the teachers, who often have questions, see the possibilities of a coherent performance between Education and the Gender and sexuality connections.